Are budgets useful? A survey of Malaysian companies - Nik Ahmad, Nik Nazli; Sulaiman, Maliah; Mohd Alwi, Norhayati (Emerald Group Publishing Limited, 2003)
This study examines if budgets are still used in Malaysian companies. There are two divergent views on the usefulness of budgets. Proponents of budgets argue that they are still relevant and useful. Meanwhile, critics claim that budgets are obsolete. They study uses the instrument developed by Drury et al. Results are compared to those of Guilding et al. The results show that budgeting practices in Malaysia are similar to those in the UK and New Zealand. There are only three major differences. First, Malaysian managers appear to feel that a participative approach to budgeting may encourage budget padding. Second, a much higher percentage of respondents compared to the Guilding et al's study, agree that top management should evaluate performance mainly on ability to achieve budgetary goals. Finally, companies in Malaysia appear to use flexible budgets more than those in the UK and New Zealand.